Positive Youth Development: Developing, Implementing, and Sustaining Music-Based Services for Emerging Adults Experiencing Homelessness. Issue 5 (October 2019) - Kelly, Brian L.
Research suggests that comprehensive services that consider the complex and interconnected needs of emerging adults experiencing homelessness may be more effective than interventions with a singular focus. There is little research that demonstrates how agencies that implement programs for individuals experiencing homelessness develop and sustain meaningful services for emerging adults, especially under conditions of increasing austerity. This study targets this gap in the literature by investigating how one transitional living program for emerging adults experiencing homelessness developed a music studio. Specifically, this study examines the factors and processes that were involved in developing, implementing, and sustaining the music studio. Findings suggest an ongoing organizational commitment to Positive Youth Development plays an important role.